Respuesta :
x + 2y = 11
x - 2y = -1
---------------add
2x = 10
x = 10/2
x = 5
x + 2y = 11
5 + 2y = 11
2y = 11 - 5
2y = 6
y = 6/2
y = 3
solution is : (5,3)
x - 2y = -1
---------------add
2x = 10
x = 10/2
x = 5
x + 2y = 11
5 + 2y = 11
2y = 11 - 5
2y = 6
y = 6/2
y = 3
solution is : (5,3)
Answer:
The solution is (5, 3)
Step-by-step explanation:
Given two equations
[tex]x+2y=11....(1)[/tex]
[tex]x-2y=-1...(2)[/tex]
we have to solve the above equations using elimination method.
Adding equation 1 and 2
[tex]x+2y+x-2y=11-1[/tex]
[tex]2x=10[/tex]
Dividing by 2, we get
[tex]x=\frac{10}{2}=5[/tex]
(1) implies x+2y=11
[tex]5+2y=11[/tex]
[tex]2y=6[/tex]
[tex]y=\frac{6}{2}=3[/tex]
hence, the solution is (5, 3)